Navegabilidad del Río Magdalena y competitividad de la logística del transporte en Colombia (2018)
The Magdalena River is the largest water tributary that Colombia has, crossing the geography of the country from the south to the north, to later flow into the Atlantic Ocean, becoming an im-portant hub for the transportation of goods in Colombia. The article analyzes the current situation of navigability of the river, and proposes a road map that contributes to increase the competitive-ness levels of the freight transport logistics from the improvement of its navigability, to be able to take advantage of its full potential, and achieve to turn it into the axis of a logistic network that articulates the fluvial ports with the port of Cartagena.